Estratégias interativas docentes em fóruns de discussão do ensino a distância: uma abordagem enunciativa - Vasconcelos, Gregório Pereira de (2012)
The spacial and temporal distance among subjects is one of the big challenges to the development of dialogues on virtual learning enviromnents (VLE) of distance teaching. Among the instruments present on Moodle platform, the VLE used by Courses offered by UFPB Virtual, the Discussion forum presents as the space that makes possible to develop social inter-relations about the contents of the discipline or other aspects. However, this instrument is not always used by teachers to develop dialogues on the respective disciplines. Many teachers apply specific question and ask students only to publish their answers. So, this study analises docent interactive strategies used on Discussion forums of distance teaching, on the discipline Introdução à Educação a Distância from the Curso de Graduação em Ciências Naturais (Licenciatura a Distância) of UFPB Virtual, during the semester 2011.2, with the intention of verifying the focus of docent interactive strategias on the referred technological instrument. It was based on the theory of enunciation of Bakhtin/Volochínov ([1929] 2010) and Bakhtin ([1979] 2010), whose perspectives conceives that the subject is constructed in relation with the alterity and on assumptions from Belloni (2009), Moran (2002, 2003, 2007, 2011) and Moore ([1993] 2002), among others, about Distance Education. We collected the corpus from the social environment where they were created and published, i.e., the own Discussion forums from the discipline mentioned above. The qualitative methodology was used to analyze the referred object of study. During the investigation of interactive strategies, we noticed that the way the teacher guides the student s participation refracts the organization of ideological practices on student-student inter-relations promoted on the discipline Introdução à Educação a Distância. Therefore, we consider that the docent interactive strategies suggest the construction of student s arguments through the dialogical and valorative relations with other discourses and subjects, influenced by the enunciative conditions determined by each situation of social communication.